Hubungan Antara Gaya Kepemimpinan Kepala Ruang Dengan Kepuasan Pasien Rawat Inap Di Kelas 1, 2 Dan 3 Rs Pku Muhammadiyah Surakarta - Isfahani, Faizal Indra; , Supratman, SKM., M.Kes., Ph.D (2016)
In a daily life of society is always near with the needs of services. One kind of services that needed by society is health service. Today the public awareness of health care services quality and comfortable is increased, so it needs to be improved in order to ensure effective implementation of health care becomes better and satisfy the society. Patient satisfaction is an important thing that used to observe service quality of hospital. Management of hospital was made in order to get patient satisfaction. Management is a system that designed to reach a goal by other's effort. In nursing management, there are some levels such as nursing top manager, nursing middle manager, and first line manager. First line manager has many kind of leadership style. Leadership style is a way of work and behavior in guiding subordinate to do something. This study was aimed to know is there any correlation between first line manager's leadership style with inpatient client satisfaction in ward class 1, 2 and 3 PKU Muhammadiyah Hospital of Surakarta. This study was quantitative non experimental research. Method that used in this study was cross-sectional. Samples were chose by proportional random sampling technique. Samples of this study were 30 inpatient clients, 30 nursing staffs and 4 first line managers that suitable with inclusion criteria. The result showed that 5 clients (100%) in ward with first line manager that has autocratic leadership style got medium satisfaction. In democratic leadership style the highest distribution was patient with high satisfaction as many 19 patients (76%) and 6 patients (24%) got medium satisfaction. Result of Fisher Exact Test showed that sign. p = 0,003, so that there was correlation between first line manager leadership style with inpatient client satisfaction. In suggestion, hospital managerial should do an effort in order to increasing first line manager skill of creating a good leadership style that suitable with the situation and condition of the room, for example included them into leadership workshop.